101k views
5 votes
Rewrite the equation by completing the square4x^2 + 28x + 49 = 0(x+__)^2 =___

1 Answer

4 votes

Given the expression;

4x^2 + 28x + 49 = 0

We are to rewrite using the completing the square method

First we need to subtract 49 from both sides of the equation

4x^2 + 28x + 49-49 = 0-49

x^2 + 28x = -49

Next is to add the square of the half of the coefficient of x to both sides of the equation as shown;

Add {1/2(28)}^2 = 14^2 = 196

The equation becomes

x^2 + 28x + 196= -49 + 196

On factorizing;

(x+14)^2 = 147

hence the required equation is (x+14)^2 = 147

User Sampath
by
4.6k points